QUESTIONING THE “KOREAN WAVED” HIJAB STYLE IN INDONESIA: A CONTEMPORARY QUR’ANIC APPROACH - Egi Tanadi Taufik; Siti Mufidatunrofiah; Nazifatul Ummy Al Amin (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2020)
Innovations on hijab have implications for the expansion of its users. Thus it encourages the growth of new identities for hijab which are then expressed by enriching its style, form, color tone, and fabric. The cultivation of hijab throughs the pop-culture of Korea arose and known as the “Korean waved” hijab. This paper has an opportunity to elaborate on hijab’s contemporary progression worldwide. It reflects the Korean pop-culture and identifies the authenticity of the tradition of wearing the hijab in Indonesia. It problematizes the issue of Korean hijab style and how the Quran responds to it. The research framework used a sequential exploratory model henceforth resulting in a scientific response to the phenomenon of Korea's creative industries in the making of an authentic Indonesian hijab model. The results answered the challenges of the vision of